Bioconversion of Sludge From Integrated Paper and Pulp Industries - Dr.S.P.S.BISHT; B.PRAVEEN; Y.RAJESH; SUBHASISH SAHOO (International Journal of Pharma and Bio Sciences, 2010)
Bioconversion is the environmentally sound alternate available for the stabilization and ultimate disposal of sludge. The main objective of the present study is to contextualize the knowledge, application and investigate systems for the onsite treatment of organic waste through bioconversion by Vermicomposting. A blend of primary and secondary sludge of 80:20 and 60:40 ratios respectively from integrated pulp and paper mill was used for composting separately with and without food and nutrients. It was observed that blend in ratio of 80:20 with food and nutrients proved to be very useful as value added compost. Further bioactivity of these blends was performed through microbial assay.